2002
DOI: 10.1128/jvi.76.5.2036-2042.2002
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of the Crm1 Nuclear Export Factor Is Sufficient To Induce Cytoplasmic Expression of Incompletely Spliced Human Immunodeficiency Virus mRNAs

Abstract: Cytoplasmic expression of the incompletely spliced RNA transcripts that encode the late, structural proteins of human immunodeficiency virus type 1 (HIV-1) is dependent on the viral Rev regulatory protein. General agreement exists that Rev acts, at least in part, by recruiting the cellular Crm1 nuclear export factor to HIV-1 transcripts bearing the Rev response element RNA target, and thereby inducing their nuclear egress. However, several groups have argued that Crm1 recruitment may not be sufficient for Rev … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 52 publications
0
44
0
Order By: Relevance
“…Rev is also known to bind nucleoporins (29 -32), and recently, it has been shown that a kinesin-like protein binds to the NES of Rev and stimulates the activity of the protein (33). Although several cofactors are likely to intervene in the RNA export process mediated by Rev, hCRM1 and Ran have been shown to be sufficient to induce translocation to the cytoplasm of incompletely spliced HIV mRNAs (34,35).…”
Section: Hiv-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Rev is also known to bind nucleoporins (29 -32), and recently, it has been shown that a kinesin-like protein binds to the NES of Rev and stimulates the activity of the protein (33). Although several cofactors are likely to intervene in the RNA export process mediated by Rev, hCRM1 and Ran have been shown to be sufficient to induce translocation to the cytoplasm of incompletely spliced HIV mRNAs (34,35).…”
Section: Hiv-1mentioning
confidence: 99%
“…Rev is also known to bind nucleoporins (29 -32), and recently, it has been shown that a kinesin-like protein binds to the NES of Rev and stimulates the activity of the protein (33). Although several cofactors are likely to intervene in the RNA export process mediated by Rev, hCRM1 and Ran have been shown to be sufficient to induce translocation to the cytoplasm of incompletely spliced HIV mRNAs (34,35).By considering that both Tat and Rev are small proteins that act through protein-protein interactions, we reasoned that it should be feasible to inhibit their function, which is absolutely necessary to viral replication, with peptide ligands competitively interfering with the associations in which they are engaged. Because it has the interest of reporting the interaction…”
mentioning
confidence: 99%
“…The leucine-rich NES in bearing proteins, like HIV-1 Rev, mediates CRM1 recruitment for nuclear export (14,47,50). Based on the analysis of amino acid sequence, Naf1 was predicted to contain four putative NESs that interact with CRM1 (51).…”
Section: Disruption Of Ness or Nls Of Naf1mentioning
confidence: 99%
“…These incompletely spliced HIV-1 RNAs contain a Rev response element (RRE), and the coordinate assembly of multiple Rev molecules on RRE recruits human protein complex containing CRM1 and Ran-GTP (GTP-binding nuclear protein Ran). Rev contains a leucine-rich nuclear export signal (NES) domain located near the carboxyl terminus, through which Rev interacts with CRM1, and the Rev-RRE-CRM1/Ran-GTP complex is then transported to the cytoplasm (6,(11)(12)(13)(14)(15)(16). Similarly, other retroviruses such as mouse mammary tumor virus and human T cell lymphotropic virus encode Rev-like regulatory proteins Rem or Rex, respectively, for hijacking the host CRM1 pathway to accomplish nuclear export of unspliced viral transcripts (17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Alternatively, cells were cotransfected with pgTAT and pCMV⌬CAN, a plasmid that expresses a truncated form of the nucleoporin CAN/Nup214 (⌬CAN). ⌬CAN blocks the ability of CRM1 to interact with the nuclear pore complex (NPC) and inhibits the nuclear export of Rev (Fornerod et al 1997;Bogerd et al 1998;Yi et al 2002). The intracellular distribution of tat RNA was visualized using a fluorochrome-labeled oligonucleotide probe complementary to stem loop IIB of the HIV-1 RRE.…”
Section: A Dominant-negative Hrip Mutant Interferes With Rev Functionmentioning
confidence: 99%